1995
DOI: 10.1021/jm00015a009
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Mimetics of Thyrotropin-Releasing Hormone Based on a Cyclohexane Framework: Design, Synthesis, and Cognition-Enhancing Properties

Abstract: The design and synthesis of peptide mimetics of thyrotropin-releasing hormone (TRH) in which the peptide backbone is entirely replaced by a cyclohexane framework are described. The cis-1,3,5-trisubstituted ring was expected to permit key pharmacophoric groups to adopt conformations consistent with proposed bioactive conformations of the peptide. Compounds were synthesized by a stereoselective synthesis starting from L-glutamic acid. In a behavioral model of cognition in which TRH is active, the mimetics are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…they did not exhibit endocrine activity. These studies, therefore, suggested that the conformation is the determinant of cognitive activity and that binding to the micromolar affinity binding site in rat brain slices is distinct from, and probably unrelated to, binding to TRH-R [29].…”
Section: Backbonementioning
confidence: 98%
See 2 more Smart Citations
“…they did not exhibit endocrine activity. These studies, therefore, suggested that the conformation is the determinant of cognitive activity and that binding to the micromolar affinity binding site in rat brain slices is distinct from, and probably unrelated to, binding to TRH-R [29].…”
Section: Backbonementioning
confidence: 98%
“…Interestingly, although the presence of the specific basic, aromatic and steric properties of the imidazole side chain of the central histidine is regarded as a decisive factor in the binding of TRH to TRH-R1, and hence for the full thyrotropin releasing activity [28], the imidazole NH appears not to be essential for cognitive effects in the Morris water maze model as mentioned below [29].…”
Section: Histidinementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Bélanger and Dufresne implemented this proposal, describing non-peptidic mimic 1 (Figure 1) of the enkephalins (see 4 and 5 , Figure 2) that incorporated the bicyclo [2.2.2]-octane scaffold 8. Later, Olson and collaborators reported peptidomimetic 2 (Figure 1), which was designed to mimic the tripeptide thyroid releasing hormone (TRH) 9. Although 2 did not bind the endocrine receptor for which it was designed, it showed oral activity in animal models of cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…This was readily accomplished by replacing Lys 9 with Phe 9 ( 12 , Figure 10) or p -F-Phe 9 ( 13 ) 14d. These results, though pleasing, raised new questions.…”
Section: Introductionmentioning
confidence: 99%